Demographic processes and anthropogenic threats of lithophytic cacti in eastern Brazil - Hughes, Frederic M.; Figueira, José E. C.; Jacobi, Claudia M.; Borba, Eduardo L. (Revista brasileira de botânica, 2018)
We contrasted the demographic trends of three congeneric populations of globose cactus—two of Melocactus ernestii Vaupel (MeC, MeM), and one of Melocactus bahiensis (Britton & Rose) Luetzelb. (MbC)—using survival, growth and reproduction data. Censuses were performed every 2 months in the three populations over a 2-year period (2011–2013 for MeM and MbC, and 2007–2009 for MeC). Two annual size–stage transition matrices and a mean transition matrix for each population were constructed to determine and compare the influence of key life cycle stages, demographic processes, harvest intensity, and pollinator decline. The populations differed in size–stage distributions, flower and fruit production, and size at maturity. The survival curves for the populations of M. ernestii did not differ from each other, but they both differed from the curve for M. bahiensis , which was higher. Based on stochastic simulations, the growth rate ( λ ) of the MeC population exceeded that of MeM. Retrospective perturbation analyses (life table response experiments, LTRE) showed that adult survival and fecundity were the main contributors to the spatiotemporal differences in λ among populations. Demographic behavior of the three populations was strongly dependent on adult survival counteracting high mortality in early stages; adult annual harvest rates > 10% would cause rapid decline in the three populations. Susceptibility to adult harvesting and high habitat specificity contributes to the populations risk of local extinction and such threats should be monitored to safeguard them.